Achieving excellent thermally conductive and electromagnetic shielding performance by nondestructive functionalization and oriented arrangement of carbon nanotubes in composite films. (7th July 2020) - Wang, Zhi-Guo; Yang, Yu-Liang; Zheng, Zi-Li; Lan, Ri-Tong; Dai, Kun; Xu, Ling; Huang, Hua-Dong; Tang, Jian-Hua; Xu, Jia-Zhuang; Li, Zhong-Ming
Abstract: Effective heat dissipation capacity and electromagnetic interference (EMI) shielding performance are urgently required for modern electronic equipment. Herein, pristine carbon nanotubes (CNTs) were first nondestructively functionalized by eco-friendly dopamine chemistry, which maintained the integrity of inherent graphitic lattice structure of CNTs. In the meanwhile, introduction of polydopamine (PDA) improved interfacial interaction between PDA-coated CNTs (CNT@PDA) and the ethylene-vinyl acetate copolymer (EVA) matrix. Favorable pathways for rapid thermal conduction and electron transmission were paved by oriented arrangement of CNT@PDA. As a result, dual-functional CNT@PDA/EVA composite films were fabricated, which exhibited remarkable in-plane thermal conductivity (TC) and prominent EMI shielding effectiveness (EMI SE). The TC and EMI SE of the 70 wt% CNT@PDA/EVA composite film climbed up to 17.9 W/mK and 32.4 dB, respectively. Furthermore, the CNT@PDA/EVA composite films revealed outstanding flexibility and mechanical fatigue durability. After repeated bending test, the retention ratio of the in-plane TC and EMI SE was 98% and 97%, respectively. The in-plane TC and EMI SE presented excellent retention ratio of 94% and 95% after repeated tensile test, respectively. Our work provides a valuable reference to design and fabricate dual-functional or multifunctional composites applied in modern electrical systems and electronic devices.